The Book-to-Market and Size Effects in a General Asset Pricing Model: Evidence from Seven National Markets - Maroney, Neal; Protopapadakis, Aris (Review of Finance, 2002)
Abstract The positive relation of returns with Book-to-Market ratio ( BE / ME ) and their negative relation withMarket Value( MVE ) remains strong under a general stochastic discount function (SDF) that does not depend on a specific asset pricing model and avoids potentially serious simultaneity biases inherent in the Fama and French three-factor model. However, we find that SDF s that include the equivalent of the HML portfolio do not span all asset sub-spaces, even with additional conditioning information. Finally, macro and financial variables we introduce to the pricing functions do not offer an alternative explanation of the BE / ME effect. JEL Classification codes: G10, G12, G15, G30.